Courageous leadership (Assemble You, 2022)
Welcome to Audio Learning from Assemble You. Being a courageous leader demands facing challenging situations with honesty and compassion. Being willing to seek out the perspectives of others to inform your own decision-making. And being just as open to receiving feedback as you are to giving it out. Courageous leaders must be willing to be authentic and vulnerable while also maintaining an open and curious mindset and acting with high emotional intelligence. In this track, we cover everything you need to know to become a courageous leader. Learning Objectives Discover what makes a courageous leader Acknowledge the impact a courageous leader can have on those they lead Identify the specific areas to work on to achieve courage in your own leadership.